Traduction des textes de spécialité comme méthode d’apprentissage des langues de spécialité Specialist Text Translation as a Method of Teaching Specialist Languages - Walkiewicz, Barbara (Glottodidactica, 2012)
Learning a specialist language entails developing a number of linguistic competencies, the most important of which is discursive competence enabling proper communication in a particular professional environment. Its development requires that the learner should become sensitive to the pragmatic aspects of specialist language use in a wider discursive context, with particular attention to genre norms forming a discursive polisystem of a given culture. This paper presents specialist text translation as one of the most effective ways of teaching a specialist language by improving discursive competence.